Peptide composition, oxidative and insecticidal activities of nectar from flowers of Spathodea campanulata P. Beauv - Santos, Valter H.M. [UNESP]; Minatel, Igor O. [UNESP]; Reco, Paulo C.; Garcia, Alexandre; Lima, Giuseppina P.P. [UNESP]; Silva, Regildo M.G. [UNESP] (Elsevier, 2017)
The growing demand for food has intensified the search for compounds of plant origin to protect field crops from predators and pathogens, as these compounds have less environmental impact and are considered healthier than synthetic compounds. Among plant species with insecticidal activity, Spathodea campanulata has been identified as a potential source of insecticidal compounds. Therefore, in this study we verified the insecticidal effect of nectar from S. campanulata against three different insects. In addition, the oxidant activity of nectar and proteomic assay were conducted to identify the insecticide potential. Both gross and dialyzate nectar showed a promising toxic effect against Euschistus heros (Fabr.), Helicoverpa zea (Boddie) and Anticarsia gemmatalis (Hübner) insects. According to oxidant tests, non-denatured nectar showed a higher oxidant activity than denatured nectar, in both albumin degradation and TBARS tests. SDS-PAGE and 2D-PAGE were used to characterize the nectar proteins, revealing 13 spots that were compatible to either proteins or peptides. The most relevant spots were analyzed by mass spectrometry, confirming the presence of proteins associated with insecticidal activity. In conclusion, it is hypothesized that S. campanulata nectar has insecticidal effects and this activity is linked to the classes of pro-oxidant proteins or peptides present in its chemical composition.
Keywords: Insecticidal tests; Nectar; Oxidant tests; Peptides; Protein characterization; Proteomics